DETERMINANTS OF REPURCHASE INTENTION ON SOCIAL COMMERCE - Yuliawan, Eko; Wahyu Widayat, Eko; Aziz Winardi, Muhammad (UNIVERSITAS INDRAPRASTA PGRI, 2024)
This study analyzes the factors influencing purchase intent and repurchase in social commerce. The main goal is to understand the contribution of variables such as ease of use, performance expectations, social Influence, and risk perception to consumer behaviors. The number of research samples was 120 respondents. The analysis method used is a partial least squares structural equation respondent, which allows researchers to measure and validate constructs and explain relationships between variables. The results showed that initial purchase intention significantly positively impacted repeat purchase intent, contributing to 55.8%. The variables of ease of use and performance expectations also influenced purchase intent significantly. While social Influence is insignificant, risk perception is a mediator that reinforces the relationship between initial and repeat purchase intent. The implications of these findings include practical advice for companies in designing marketing strategies, product development, and customer management. The marketing strategy should be focused on communicating ease of use and product performance expectations. Companies must also understand and manage consumer risk perceptions to build trust and increase repeat purchase intent. These implications guide practitioners and researchers in understanding the dynamics of consumer behaviors in a broader context.